2010
DOI: 10.1371/journal.ppat.1001091
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of Ligand-Gated Ion Channels Predicts Monepantel Effect

Abstract: The recently launched veterinary anthelmintic drench for sheep (Novartis Animal Health Inc., Switzerland) containing the nematocide monepantel represents a new class of anthelmintics: the amino-acetonitrile derivatives (AADs), much needed in view of widespread resistance to the classical drugs. Recently, it was shown that the ACR-23 protein in Caenorhabditis elegans and a homologous protein, MPTL-1 in Haemonchus contortus, are potential targets for AAD action. Both proteins belong to the DEG-3 subfamily of ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 51 publications
2
50
0
1
Order By: Relevance
“…Remarkably, Tua3 has an atypical FxCC amino acid motif ( Figure S1), instead of the highly conserved YxCC in loop C. A study of the chicken a7 nAChR receptor expressed in Xenopus oocytes showed that changing the YxCC motif to FxCC, resulted in a tenfold decrease in ACh affinity (Galzi et al, 1991). The unusual FxCC motif was previously also identified in nAChR(s) of Tribolium confusum, N. vitripennis and the nematodes C. elegans and Haemonchus contortus Rufener et al, 2010). Future functional studies should point out if the presence of this motif in arthropod and nematode nAChRs also results into a similar decrease in ACh affinity.…”
Section: T Urticae Nicotinic Acetylcholine Receptor Subunitsmentioning
confidence: 82%
“…Remarkably, Tua3 has an atypical FxCC amino acid motif ( Figure S1), instead of the highly conserved YxCC in loop C. A study of the chicken a7 nAChR receptor expressed in Xenopus oocytes showed that changing the YxCC motif to FxCC, resulted in a tenfold decrease in ACh affinity (Galzi et al, 1991). The unusual FxCC motif was previously also identified in nAChR(s) of Tribolium confusum, N. vitripennis and the nematodes C. elegans and Haemonchus contortus Rufener et al, 2010). Future functional studies should point out if the presence of this motif in arthropod and nematode nAChRs also results into a similar decrease in ACh affinity.…”
Section: T Urticae Nicotinic Acetylcholine Receptor Subunitsmentioning
confidence: 82%
“…When choline was coapplied with monepantel, the threshold of potentiation differed markedly between the different receptors. Whereas it was about 100 nM in ACR-23 channels (Rufener et al, 2013), MPTL-1 channels were about 100 times more sensitive, a difference of sensitivity toward monepantel that is also observed in vivo on worm viability: the calculated LC 50 for C. elegans is 100 nM (Rufener et al, 2010b) and 7.5 nM (data not shown) for H. contortus. This difference can be explained by the fact that monepantel has been optimized based on H. contortus efficacy in vitro and in vivo and not on C. elegans.…”
Section: Discussionmentioning
confidence: 77%
“…Recent phylogenetic studies (Rufener et al, 2010b) have shown that mptl-1 is more closely related to the C. elegans acr-20, another member of the nematode-specific deg-3 subfamily. This similarity suggests that it may function as a secondary target for monepantel.…”
Section: Introductionmentioning
confidence: 99%
“…Virtually all therapeutics currently in use for nematode control, ivermectin, levamisole and, most recently, monepantel all act through neuroreceptors of the worm's neuromuscular system (see Holden-Dye and Walker 2007;Rufener et al 2010). Praziquantel also acts, in part, by disrupting normal muscle function and causing paralysis (Greenberg 2005;Jeziorski and Greenberg 2006).…”
Section: Complications With Heterologous Expression Of Gpcrsmentioning
confidence: 99%